CHALLANGES IN TEACHING ENGLISH LITERATURE: A TEACHER'S PERSPECTIVE - Purtanto, Chika Azizah; Wahyuningtyas, Retno Tri; Rohmana, Wahyu Indah Mala (Universitas Suryakancana, 2023)
In Indonesia, teaching English through literature (literary text) in primary school has challenges because it does not have a curriculum. Especially English subject is only local content that does not have to include in primary school. A school that never implemented English in their learning must be difficult to provide teaching. So, this study aims to research the challenges in teaching English literature in primary school from a teacher’s perspective and the strategies used to solve the challenges. The method used in this research is qualitative descriptive and the subject is an English teacher of 6th grade in MI Nadlatul Ulama Malang. Data were collected through an unstructured interview via WhatsApp and met in person. The researchers analyzed the data based on the results of the interview. The research found three challenges an English teacher of 6th grade at MI Nadlatul Ulama faced in learning English literature. The three challenges are in the aspect of learning media, students English skill gap, and the time of the English lessons. Some strategies are used to make teaching done effectively. To increase students' motivation, the teacher delivered material using PowerPoint not only on the blackboard. The teacher also accompanies when students have difficulty or are confused about accepting the material provided.